Maternal and cord blood cyclophilin A in severe preeclampsia and normal pregnancy and its correlation with vitamin D and zinc - Noroyono Wibowo; Riyan Hari Kurniawan; Rima Irwinda; Natasya Prameswari (Taylor & Francis Group, 2017)
Objective: To investigate maternal and cord blood cyclophilin A level in severe preeclampsia compared with normal pregnancy and its correlation with vitamin D and zinc level. Methods: We conducted a cross-sectional observational study of pregnant women who gave birth in Cipto Mangunkusumo Hospital between January and April 2014. Results: Thirty-nine subjects were included. Subjects with severe preeclampsia have higher serum cyclophilin A levels compared with normotensive pregnancy (1299.60 vs. 1039.50; p 0.017). Maternal cyclophilin A, vitamin D, and zinc correlation were not statistically significant (p 0.189 & p 0.853). Conclusion: Cyclophilin A levels in severe preeclampsia is higher compared to normal pregnancy. There is no correlation between cyclophilin A, zinc, and vitamin D.